Connections and interlocations between self-image, self-esteem, active sexuality, and quality of life in ageing - Mônica Rodrigues da Silva; Leiner Resende Rodrigues (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to reflect on the connection between self-image, self-esteem, active sexuality, and quality of life in ageing; identify which measurement instruments in Brazilian and international literature interconnectively address the connections referred to in the general objective. Method: a theoretical-reflexive essay. Results: the reflection was described in the guiding axes: Connections between self-image, self-esteem, active sexuality, and quality of life in ageing; Interlocutions and instruments for measuring the connection between sexuality and ageing. Instruments in Brazilian and international literature are unable to address this topic in an interconnected way. Limitations and disadvantages of application with elderly individuals are presented. Final considerations: carrying out qualitative research and validating quantitative instruments that show connections and interlocutions, without stigmas and reprimands, common in this age group, should be encouraged in the scientific field and in social spaces.